Integrated valorization of Moringa oleifera and waste Phoenix dactylifera L. dates as potential feedstocks for biofuels production from Algerian Sahara: An experimental perspective. (July 2019) - Boulal, A.; Atabani, A.E.; Mohammed, M.N.; Khelafi, M.; Uguz, Gediz; Shobana, Sutha; Bokhari, Awais; Kumar, Gopalakrishnan
Abstract: The world is concerned with the degradation of the Saharan eco-system due to the absence of green spaces, emission of greenhouse gases and the burial of oases by sand beside the global energy crisis. This promoted the Algerian government to set a national strategy towards the use of renewable sources to cover 40% of its energy needs by 2030. In this article, a modern technique to simultaneously protect the environment and produce biofuels from the Saharan environment through cultivation of Moringa oleifera and valorizations of waste Phoenix dactylifera L. dates which are of not of satisfactory quality for the local market has been adopted. Characterization of Moringa oleifera oil, Moringa oleifera biodiesel and bioethanol produced from the waste date was done. Biodiesel-diesel-bioethanol blends were characterized by DSC, FT-IR, TGA and GC methods. Results show high oil content of Moringa oleifera seeds of 40%, biodiesel yield of 91% and bioethanol percentage of 96.83% with 3.17% of impurities. The properties of ternary blends of D80B5BE15, D80B10BE10 and D80B15BE5 exhibit similar densities and cold flow properties to Euro-diesel. Our analysis also proved that waste Phoenix dactylifera L. dates are useless as ruminant feed due to low protein content. In conclusion, the study proved the feasibility of cultivating Moringa oleifera to protect the environment and valorizing its seeds besides waste date seeds to produce both biodiesel and bioethanol in the Algerian Saharan. Graphical abstract: Image 1 Highlights: Moringa oleifera seeds and waste Phoenix dactylifera L. dates were valorized. Feasibility of biodiesel and bioethanol production was proved. Moringa oleifera proved to provide unlimited benefits to the environment. Due to low protein content, Phoenix dactylifera L. dates are useless ruminant feed. DSC, FT-IR and TGA of blends were investigated in details.